OD PÓŹNEGO WORONICZA DO WCZESNEGO WITTGENSTEINA. KARIERA PIEŚNI O WIKLEFIE I WIKLEFA W XIX-WIECZNEJ POLSCE - Zieliński, Jan (Colloquia Litteraria, 2017)
The article is interested in following the history of the reception of the exceptional example of fifteenth-century poetry in Polish Pieśń o Wiklefie by Jędrzej Gałka of Dobczyn in the period between the discovery of the text in 1815 and the beginning of the First World War. The author discusses the reception of Pieśń o Wiklefie in later works of the Enlightenment poets as well as in texts by Mickiewicz and Norwid (the latter was friends with the poet Antoni Czajkowski, whose father first published Pieśń o Wiklefie). The article concludes with a discussion of the intellectual contacts between the logician Michał Dziewicki – one of the publishers of Wycliffe’s works – and Wittgenstein, who served in the military in Cracow.